Jual Beli Follower Untuk Meningkatkan Branding Pada Media Sosial Instagram Dalam Perspektif Hukum Positif dan Hukum Syariah - Pazriah, Mia; Armen, Rio Erismen; Aldizar, Addys (Department of Islamic Economics Law, 2024)
This research aims to find out how positive law and sharia law reflect the practice of buying and selling Instagram follower and its objectives. This research uses a qualitative descriptive method by combining two methods, namely field and literature methods. From this research, the results obtained show that the mechanism for buying and selling follower is carried out using an electronic system where orders and payments are made to the seller using electronic devices, after which the seller will add follower using the help of a follower addition application. In positive law, this transaction is considered unlawful because it does not comply with the regulations stated in Law No. 11 of 2008 concerning Electronic Information and Transactions where follower added to the buyer's account are added without permission from the owner. The results of this research also reveal that the practice of buying and selling Instagram follower is not in accordance with sharia regulations, where this practice does not fulfill one of the conditions for buying and selling, namely that the object of the contract must belong to the seller, whereas in this research the follower who are the object of buying and selling do not belong to the seller